LAPORAN KASUS CAESAREAN SCAR ENDOMETRIOSIS : TEMUAN KLINIS HINGGA HISTOPATOLOGI - Denny Dhanardono; Yohanes Satrya Wibawa (Jurnal Akta Trimedika, 2024)
Scar endometriosis is an uncommon condition where there is functioning endometrial tissue found in the location of a surgical scar. In this report, we present a case of cesarean scar endometriosis in a 37-year-old female patient. Case presentation A 37-year-old female, with history of cesarean section, reporting cyclical pain and a noticeable bulge at the location of her previous surgical scar, particularly during her menstrual cycle. A hypoechoic mass measuring 3.8x3.2x4 cm was identified on an abdominal ultrasound. The mass is located within the subcutaneous tissue of the anterior abdominal wall, namely on the right side of a previous surgical scar. The patient was scheduled for surgical excision of the tissue. The histopathology result of the specimen from the operation showed connective and fat tissue with visible endometrial glands and stroma. Discussion Scar endometriosis is an uncommon condition. The occurrence of the hormone sensitive endometrial tissue being implanted into the edge of the wound after surgery is best explained by iatrogenic factors. Typically, they manifest as a painful lump at the location of a surgical scar that experiences recurring changes in size and intensity in sync with the menstrual cycle. Radiography might be used to confirm the diagnosis. Treatment options can be categorized as medical or surgical, with the latter being more efficacious and the recommended choice. Conclusion Cysts caused by endometriosis in caesarean scar are extremely uncommon. The clinical manifestations may be less apparent, and the diagnosis primarily depends on the patient's prior surgery history and imaging. If a mass is discovered in the area of the previous caesarean scar, whether or not there are indications of monthly abnormalities and occasional abdominal pain, it should be regarded as an endometriotic cyst at caesarean scar. Opting for surgical intervention is a favorable decision for addressing this ailment.